Influence of Cu Content Variation on the Tribological Properties of Ni60CuMo with Sandwich-Structured Composite Coatings by Laser Cladding - Fengqin Ji; Xincheng Li; Songyang Zhang; Ming Pang (Micromachines)
To enhance the tribological properties of the coatings and to inhibit cracking, sandwich-structured composite coatings were fabricated, consisting of a Ni60CuMo/IN718 transition layer and a Ni60CuMo/Ni-coated Cu wear-resistant layer with four different Ni-coated Cu contents. The results indicate that the transition layer inhibits the crack formation in the coating, and the refined grain structure stabilizes its average hardness at approximately 485 HV0.5. Increasing the Cu content in the wear-resistant layer exacerbates the segregation of the Cu-rich solid solution phases and refines the in situ-generated Cr7C3, TiC, and NbC phases. The average hardness of the wear-resistant layer decreases from 474 HV0.5 to 408 HV0.5 as the Ni-coated Cu content increases from zero to 75%. The coating with 50% Ni-coated Cu has the best Cu self-lubricating properties and exhibits the best wear resistance at both room and high temperatures. At room temperature, abrasive wear is the primary wear mechanism in the coatings. Although the ductility of the coatings is improved with increasing Cu content, excessive Cu reduces the hardness and load-bearing capacity. At 300 °C, oxidation wear becomes the dominant wear mechanism, accompanied by plastic deformation and three-body wear as the Cu content increases. At 500 °C, severe oxidation wear is the dominant mechanism, with excessive Cu leading to oxidation film failure.